2019
DOI: 10.14710/jitaa.44.2.167-176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of napier grass supplemented with Gliricidia sepium, Sapindus rarak or Hibiscus rosa-sinensis on in vitro rumen fermentation profiles and methanogenesis

Abstract: ABSTRAKPenelitian ini menguji efek suplementasi daun gamal (DG, Gliricidia sepium), buah lerak (BL, Sapindus rarak), atau daun kembang sepatu (DKS, Hibiscus rosa-sinensis) pada rumput gajah (RG, Pennisetum purpureum) terhadap fermentasi rumen dan metanogenesis secara in vitro. Rancangan percobaan yang dilakukan adalah rancangan acak kelompok dengan tujuh perlakuan dan empat ulangan. Perlakuan yang diujikan meliputi: RG, DG, BL, DKS, RG 70% + DG 30%, RG 70% + BL 30%, dan RG 70% + DKS 30%. Peubah yang diamati ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
3
0
3
Order By: Relevance
“…Acetic acid becomes the main substrate for Methanobacterium and Archaea in rumen methanogenesis [42]. However, the CH4 profile was lower than when Hibiscus rosa-sinensis leaves and Sapindus rarak fruits with saponin levels of 16.6 -36.4 % DM were used, which had methane production levels of 36.8 and 35.1 % of total VFAs, respectively [43]. Suriyapha et al [44] reported that bamboo grass (Tiliacora triandra) pellet supplements used as a rumen modifier at 150 g/head/d produced CH4 ranging from 26.0 -30.5 CH4 mmol/100 mol.…”
Section: Effect Of Pre-ingestive Citronella Residue On In Vitro Rumen...mentioning
confidence: 99%
“…Acetic acid becomes the main substrate for Methanobacterium and Archaea in rumen methanogenesis [42]. However, the CH4 profile was lower than when Hibiscus rosa-sinensis leaves and Sapindus rarak fruits with saponin levels of 16.6 -36.4 % DM were used, which had methane production levels of 36.8 and 35.1 % of total VFAs, respectively [43]. Suriyapha et al [44] reported that bamboo grass (Tiliacora triandra) pellet supplements used as a rumen modifier at 150 g/head/d produced CH4 ranging from 26.0 -30.5 CH4 mmol/100 mol.…”
Section: Effect Of Pre-ingestive Citronella Residue On In Vitro Rumen...mentioning
confidence: 99%
“…Durante el proceso de fermentación in vitro, el gas que se genera es resultado del metabolismo microbiano y su volumen depende de las características físico químicas del sustrato presente en el rumen (Yuliana et al, 2019). Los mayores volúmenes de gas encontrados con el uso de follaje, principalmente con la inclusión de G. ulmifolia (T4) y H. rosa-sinensis (T5), pudo verse favorecido por un mejor aporte en la proteína y energía disponible en las dietas, promoviendo una mayor actividad microbiana y un menor tiempo de colonización del sustrato; principalmente por un aumento en la concentración de proteína soluble, de nitrógeno no proteico disponible y de carbohidratos como almidón, pectinas y azúcares solubles; los cuales ocasionaron un rápido inicio de la fermentación (Tabla 4), que se mantuvo durante 24 horas; dando como resultado una mayor digestibilidad de la materia orgánica (Albores-Moreno et al, 2019;Jiménez-Guillen et al, 2020;Molina-Botero et al, 2020).…”
Section: Fermentación Y Producción De Gas In Vitrounclassified
“…Contrario a los resultados encontrados en este estudio, Yuliana et al (2019) reporta que una mezcla de 30% H. rosa-sinensis y 70% de P. purpureum no mejora la producción de gas in vitro en las primeras 24 h y 48 h de incubación. Esta divergencia en los resultados podría deberse al efecto que ejerció la incorporación de harina de yuca, que posee altos contenidos de almidón y azúcares solubles, y que pudieron promover un rápido crecimiento de los microorganismos.…”
Section: Fermentación Y Producción De Gas In Vitrounclassified
See 1 more Smart Citation
“…Previous researchers have done several experiments to reduce methane gas production, namely through concentrate supplementation (Lovett et al, 2005), lipid (Ungerfeld et al, 2005), forage supplementation containing tannins , use of natural additives (Jayanegara, 2011). Studies on using natural compounds, such as tannins, saponins, and essential oils, are increasingly being carried out in line with the banning of antibiotics (Yuliana et al, 2019).…”
Section: Introductionmentioning
confidence: 99%